2007
DOI: 10.1016/j.cellimm.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of age-, gender- and diet-associated changes in murine thymus

Abstract: The loss of thymic function with age may be due to diminished numbers of T-cell progenitors and the loss of critical mediators within the thymic microenvironment. To assess the molecular changes associated with this loss, we examined transcriptomes of progressively aging mouse thymi, of different sexes and on caloric-restricted (CR) vs. ad libitum (AL) diets. Genes involved in various biological and molecular processes including transcriptional regulators, stress response, inflammation and immune function sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…CR delays thymic involution in mice (Jolly, 2004;Yang et al, 2009;Lustig et al, 2007) and also decreases the production of PGE 2 (Meydani et al, 1990). As anticipated this leads to greater T lymphocyte production and activity in later life, and to a reversal of the age related reduction in IL-2 production in mice under CR.…”
Section: Immune Systemmentioning
confidence: 55%
“…CR delays thymic involution in mice (Jolly, 2004;Yang et al, 2009;Lustig et al, 2007) and also decreases the production of PGE 2 (Meydani et al, 1990). As anticipated this leads to greater T lymphocyte production and activity in later life, and to a reversal of the age related reduction in IL-2 production in mice under CR.…”
Section: Immune Systemmentioning
confidence: 55%
“…Conclusions generated from previous investigations conflict regarding the association between the effects of CR and aging. On the one hand, an early investigation revealed that age-associated expression patterns in muscle were "either completely or partially prevented by caloric restriction" [19], and this conclusion was supported in subsequent studies [14,20,21]. Other investigations, however, have yielded different conclusions.…”
Section: Introductionmentioning
confidence: 93%
“…It is likely that, given the complexity of immune system development, the number of cells involved in an immune response (and especially the changes in the immune system with aging), multiple genetic loci, and many genes will contribute to agerelated changes in immunity (46). Furthermore, recent studies investigating the molecular mechanisms associated with thymic aging showed the necessity of taking biological variables such as gender and diet into account when studying the role of genomics in the molecular pathways responsible for thymic involution (62). The use of model organisms facilitates testing different hypotheses regarding the role of genetics in immune responses.…”
Section: Human Longevity Genetics and Inflammationmentioning
confidence: 99%